Autoimmunity in Guillain-Barré syndrome associated with Zika virus infection and beyond (2017)
Autoimmune diseases share common immunopathogenic mechanisms (i.e., the autoimmune tautology), which explain the clinical similarities among them as well as their familial clustering. Guillain-Barré syndrome (GBS), an autoimmune peripheral neuropathy, has been recently associated with Zika virus (ZIKV) infection. Based on a series of cases, this review article provides a comparative analysis of GBS associated with ZIKV infection, contrasted with the general characteristics of GBS in light of the autoimmune tautology, including gender differences in prevalence, subphenotypes, polyautoimmunity, familial autoimmunity, age at onset, pathophysiology, ecology, genetics, ancestry, and treatment. © 2017 Elsevier B.V.